Cybersovereignty: The Example of China (Texas Journal of Multidisciplinary Studies, 2022)
This article explores the concept of understanding of countries’ sovereignty on the web space, based on the example of the People’s Republic of China and influence of globalization process to comprehension of sovereignity. Territorial sovereignty can be easily recognised by territorial borders, however a country's cyber sovereignty involves a more complex approach to limiting it. In addition, there is currently no exact binding law regulating and defining the scope of cybersovereignty. From a historical perspective, China, as a developed country, was one of the first countries, which introduced the Internet into its states And therefore, s strict system of control and restriction of Internet use, called the Golden Shield, was introduced to regulate legal relations in the Internet sphere. This system imposes censorship, restrictions of anonymity, and practice of banning unnecessary web domains and VPN services. Whether such a system is effective in terms of reducing crime on the one hand or on the other hand making the political environment in the country more fragile. The purpose of this article is to reveal the essence of the concept of cyberspace, the extent to which it is developed, what restrictions states are entitled to impose on Internet space and to examine China's practices and their consequences.